2002
DOI: 10.1177/104063870201400603
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mycoplasma Hyopneumoniae Nested Polymerase Chain Reaction Test to Determine the Optimal Sampling Sites in Swine

Abstract: A number of polymerase chain reaction (PCR)-based diagnostic tests have been developed for Mycoplasma hyopneumoniae, including one from this research group. This report presents further development, optimization, and standardization of a nested PCR test. Detection sensitivity was 1 fg of M. hyopneumoniae chromosomal DNA (approximately 1 organism). This exceeded the sensitivity of or compared favorably with other published PCR tests. Polymerase chain reaction primers to porcine 2-microglobulin were included as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 18 publications
9
59
1
9
Order By: Relevance
“…This chromosomal region involved mhp024 and included both a deletion and sequence variation. The region was identified using a nested PCR test that failed to identify these two strains with the inner primer pair (11). It is significant that the present study confirmed the variation within mhp024 in one of these strains (00MP1502), and the data are just outside our q value cutoff for 00MP1301 (P Ͻ 0.0053, q Ͻ 0.234) since the regions containing this sequence variation are represented on the array.…”
Section: Discussionsupporting
confidence: 57%
“…This chromosomal region involved mhp024 and included both a deletion and sequence variation. The region was identified using a nested PCR test that failed to identify these two strains with the inner primer pair (11). It is significant that the present study confirmed the variation within mhp024 in one of these strains (00MP1502), and the data are just outside our q value cutoff for 00MP1301 (P Ͻ 0.0053, q Ͻ 0.234) since the regions containing this sequence variation are represented on the array.…”
Section: Discussionsupporting
confidence: 57%
“…We used the positive results in the BAL fluid for the calculation of the R n because this is believed to be the most sensitive parameter to predict an infection with M. hyopneumoniae at individual level (Kurth et al, 2002). Nasal swabs were not used since results are less reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Also included were single isolates of several infrequently identified mycoplasmas and acholeplasmas of swine and of Mycoplasma bovis from cattle. Clinical samples were obtained from pigs experimentally inoculated with different isolates of M. hyopneumoniae as previously described (11,28) and from uninfected control pigs. Samples were obtained 28 days postinfection at necropsy (11).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, seroconversion to M. hyopneumoniae is often slow within a herd and can vary considerably among pigs, making the use of enzyme-linked immunosorbent assays less effective. A number of PCR assays have been developed and reported to be both sensitive and specific for M. hyopneumoniae (4,6,11,19,20,22,24,26). As a result, this technique is now among the most widely used for detection of M. hyopneumoniae in pigs.…”
mentioning
confidence: 99%